Governo eletrônico: dimensões da avaliação de desempenho na perspectiva do cidadão - Barbosa, Alexandre Fernandes (2008)
The goal of this research is to identify if the process of negotiation for the installation of two multinational companies in the state of Paraná had influence in the development of the companies' relationship with their suppliers. The negotiation processes were analyzed, taking into account the literature on Foreign Direct Investment, in particular the Bargain Model. Two essential differences were found in the processes. Globalization and the consequent opening up of the Brazilian Market, meant that the country and the state of Paraná had less bargaining power in the negotiation that occurred in the 1990's. The change in the political regime and the fiscal decentralization, that had as consequence the fiscal war, determined that Paraná's bargaining power was weaker in that decade. Volvo's smaller bargaining power in relation to Brazil and the state of Paraná in the 1970's, meant that the company developed more relationships with local suppliers. On the other hand, in the 1990's, Renault was not influenced in the same way. Therefore, as the relationship of the two companies with their suppliers was analyzed, the data showed that a significant difference was found only relating to the relationships with national and multinational suppliers. Volvo has a higher proportion of national suppliers than Renault, especially when using the control variable 'being installed in the state of Paraná'. These results make evident another of the consequences of the fiscal war, that is, a lesser degree of integration with the local organizations. Within the Social Embeddedness perspective, this lesser degree of integration with the local organizations may lead to less exchange of information between the company and the aforementioned organizations, and therefore, to a smaller degree of competence development of that subsidiary and less possibility of economical growth in the region.